2011
DOI: 10.2478/v10035-011-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Digestive System Fistula - A Problem Still Relevant Today

Abstract: Digestive system fistula originates most frequently as a complication after surgical procedures, less often occurs in the course of inflammatory diseases, but it can also result from neoplasm and injuries. THE AIM OF THE STUDY was to analyze the causes and retrospectively assess the perioperative procedures as well as the results of digestive system fistula treatment. MATERIAL AND METHODS. Own experience in digestive system fistula treatment was presented. The subject group consisted of 32 patients treated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In all four cases, conservative management was attempted, consisting of antibiotic treatment, parenteral nutrition, analgesic drugs, proton pump inhibitors and gastrostomy tube placement (in one case), followed by palliative care. In other seven cases, intestinal fistulas were reported and were surgically managed in most cases; however, in all these cases the underlying process which induced the development of fistula consisted of inflammatory bowel disease and not a neoplastic process, all patients having a good postoperative outcome (34).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In all four cases, conservative management was attempted, consisting of antibiotic treatment, parenteral nutrition, analgesic drugs, proton pump inhibitors and gastrostomy tube placement (in one case), followed by palliative care. In other seven cases, intestinal fistulas were reported and were surgically managed in most cases; however, in all these cases the underlying process which induced the development of fistula consisted of inflammatory bowel disease and not a neoplastic process, all patients having a good postoperative outcome (34).…”
Section: Discussionmentioning
confidence: 98%
“…The other particularity of our case was the association of a complex gastrocolic-cutaneous fistula at the time of presentation. Usually seen during the postoperative or postprocedural periods, complex digestive tract fistulas also occur in patients with inflammatory bowel disease or advanced neoplastic processes (8)(9)(10)(11)(31)(32)(33)(34). In the study conducted by Gluszek et al and published in 2011, 32 patients with digestive tract fistulas were included; among these cases, association of a neoplastic process was seen in four and consisted of bronchoesophageal fistula due to pulmonary or esophageal carcinoma in three cases and an enterovaginal fistula due to an anal carcinoma in one case.…”
Section: Discussionmentioning
confidence: 99%
“…Th eir bad prognosis of the patient's condition, the diffi culties of early diagnosis and the optimal choice of the therapeutic method turn them into an issue of great interest. About a third of the deaths occur due to digestive anastomoses following fi stulas [4].…”
Section: Discussionmentioning
confidence: 99%
“…Th e Charlson comorbidity index was calculated for each patient included in the study according to the method presented by Hall and Ramachandran [4].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported that antibiotic therapy and medical treatments that decrease GI tract secretions, such as somatostatin, are useful to treat these same patient groups [16,17].…”
Section: Discussionmentioning
confidence: 99%